1982
DOI: 10.1038/299838a0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of steroid sulphatase locus on active and inactive human X chromosome

Abstract: The X chromosome in mammalian somatic cells is subject to unique regulation--usually genes on a single X chromosome are expressed while those on other X chromosomes are inactivated. The X-locus for steroid sulphatase (STS; EC 3.1.6.2), the microsomal enzyme that catalyses the hydrolysis of various 3 beta-hydroxysteroid sulphates, is exceptional because it seems to escape inactivation. Evidence for this comes from fibroblast clones in females heterozygous for mutations that result in a severe deficiency of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 20 publications
1
52
0
Order By: Relevance
“…This has been shown for MIC2, the only pseudoautosomal gene identified at present (2). Two chromosome X-specific genes (XG encoding the Xg blood group and STS encoding steroid sulfatase), mapping to Xp22.3, also escape, at least partially, this inactivation (3)(4)(5). By analogy, it has been suggested that such X-specific genes from Xp22.3, which are at least partially insensitive to X-inactivation, are remnants of an ancestral pseudoautosomal region that once extended more proximally on Xp22.3.…”
mentioning
confidence: 99%
“…This has been shown for MIC2, the only pseudoautosomal gene identified at present (2). Two chromosome X-specific genes (XG encoding the Xg blood group and STS encoding steroid sulfatase), mapping to Xp22.3, also escape, at least partially, this inactivation (3)(4)(5). By analogy, it has been suggested that such X-specific genes from Xp22.3, which are at least partially insensitive to X-inactivation, are remnants of an ancestral pseudoautosomal region that once extended more proximally on Xp22.3.…”
mentioning
confidence: 99%
“…This segment is of considerable interest because in this region, a reduction of X inactivation has been observed (Mohandas et al 1979;Miiller et al 1980;Migeon et al 1982). Furthermore, this region is thought to be involved in crossover events with the distal end of the short arm of the Y chromosome (de la Chapelle 1981;Polani 1982;Burgoyne 1982).…”
Section: Discussionmentioning
confidence: 99%
“…escape inactivation (32)(33)(34)(35)(36) suggest that the process is still Ipials was initially exincomplete in some regions of the human X chromosome, am the ancestral maiperhaps because these genes lack sequences that respond to aller marsupial X chroa signal spreading from an X inactivation center. The obserriabsence also from the vation that some genes that escape inactivation in humans are ficult to explain on this inactivated in mouse suggests that the inactivation system verged earlier from the may be more completely evolved in mouse (31 …”
Section: Discussionmentioning
confidence: 99%